Pediatric Home Tracheostomy Care: The Importance of Knowledge Assessment. Issue 3 (August 2022) - Boonjindasup, Wicharn; Syananondh, Kusuma; Somboon, Prapasri; Sritippayawan, Suchada
Assessment of caregiver knowledge is an essential part of home healthcare education for pediatric tracheostomy care, however, there is a paucity of evidence in long term. This study aims to determine how caregiver knowledge and misconceptions, as assessed by our knowledge test, changed over a 12-month period following our educational program and whether the test score was associated with any demographics of the caregivers and children with tracheostomy. A prospective cohort study was undertaken to evaluate the knowledge at 3 timepoints after tracheostomy education: baseline (T1), 6 months (T2), and 12 months (T3). Test scores were analyzed for trend and relationship with demographics. Items for which less than 80% caregivers gave correct responses at T1 were considered common misconceptions. Fifty-four caregivers were enrolled. Out of a maximum score of 25, the median (IQR) scores were 22 (21-23), 23 (22-24), and 23 (22-25), at T1, T2, and T3, respectively. The scores at T2 and T3 were significantly higher than at T1 ( P ≤ .01). One common misconception "how to manage when suction got less secretion than expected" was found at all timepoints. Caregivers of children with >2 comorbidities scored slightly higher than those of children with 0 to 2 comorbidities ( P = .01). In conclusion, our caregivers achieved high knowledge scores which increased over the 12-month study period potentially because of repeated assessment and practical experience. Common misconceptions and a factor associated with the knowledge were also identified. These advantages highlighted the importance of knowledge assessment for quality improvement.